1984
DOI: 10.1056/nejm198401193100302
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Abnormalities of Cardiac Function in Progressive Systemic Sclerosis with Diffuse Scleroderma

Abstract: To investigate cardiopulmonary function in progressive systemic sclerosis with diffuse scleroderma, we studied 26 patients with maximal exercise and redistribution thallium scans, rest and exercise radionuclide ventriculography, pulmonary-function testing, and chest roentgenography. Although only 6 patients had clinical evidence of cardiac involvement, 20 had abnormal thallium scans, including 10 with reversible exercise-induced defects and 18 with fixed defects (8 had both). Seven of the 10 patients who had e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
100
0
8

Year Published

1985
1985
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 222 publications
(113 citation statements)
references
References 29 publications
5
100
0
8
Order By: Relevance
“…Although the findings from Doppler echocardiographic studies (7-1 l), radionuclide ventriculography (12-14,16), and perfusion scintigraphy (15)(16)(17)(18)(19)(20)(21)(22) in the assessment of cardiac involvement in limited SSc have been evaluated in different reports, studies providing a comprehensive approach to these noninvasive investigations in limited SSc are not available. In the present study, when patients with limited SSc were compared with those in the control group (Tables 1 and 2), the most remarkable Doppler echocardiographic findings were the high prevalence of abnormal left and right diastolic parameters, mitral regurgitation, and mitral subvalvular thickening.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the findings from Doppler echocardiographic studies (7-1 l), radionuclide ventriculography (12-14,16), and perfusion scintigraphy (15)(16)(17)(18)(19)(20)(21)(22) in the assessment of cardiac involvement in limited SSc have been evaluated in different reports, studies providing a comprehensive approach to these noninvasive investigations in limited SSc are not available. In the present study, when patients with limited SSc were compared with those in the control group (Tables 1 and 2), the most remarkable Doppler echocardiographic findings were the high prevalence of abnormal left and right diastolic parameters, mitral regurgitation, and mitral subvalvular thickening.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies using Doppler echocardiography (12) and radionuclide ventriculography (11, [13][14][15] have disclosed diastolic function abnormalities in SSc patients. Radionuclide perfusion studies using thallium-201 (11, [16][17][18][19][20][21][22] or positron emission tomography (23) have shown perfusion defects that, in the absence of coronary lesions, may be attributed to a local coronary spasm. These sustained or repeated episodes of vasospasm may be responsible for the myocardial fibrosis and contraction band necrosis that can be found in patients with SSc.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired coronary artery reserve has previously been demonstrated in SSc patients by noninvasive imaging techniques (5)(6)(7). Studies published a few decades ago suggested an underlying microvascular disease of the myocardium, based on normal findings on coronary angiogram (8) and the absence of coronary atherosclerosis upon histologic examination at autopsy (9)(10)(11)(12). However, clinical and subclinical coronary artery disease (CAD) is increasingly reported in SSc patients (13)(14)(15), although the prevalence of coronary atherosclerosis and the predisposing factors in SSc patients remain unknown.…”
mentioning
confidence: 99%
“…Arteriolar vasospasm that is analogous to Raynaud's phenomenon (RP) may lead to reversible attacks of ischemia in response to cold provocation. Alterations of the microvasculature may play a crucial role in the development of SScMI [11][12][13][14][15][16][17]. Observations suggest that coronary flow reserve (CFR) is reduced in SSc despite the lack of atherosclerotic CAD [17][18][19].…”
Section: Introductionmentioning
confidence: 99%